2018
DOI: 10.1002/mc.22933
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 7 receptor activates PI3K/Akt/mTOR signaling pathway via downregulation of Beclin‐1 in lung cancer

Abstract: Interleukin‐7(IL‐7) can regulate proliferation and apoptosis of cell and also regulate tumor lymphangiogenesis, but whether it regulating autophagy of tumor cells is not well known. We study the relationship between IL‐7 and some autophagy‐related markers, Beclin 1 and mammalian target of rapamycin (mTOR) and the mechanism of IL‐7 in regulating autophagy of human lung cancer cells. We detected expression of Beclin 1 and mTOR in lung cancer cells and their impact on the prognosis of lung cancer patients. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…IL-7 and its receptor IL-7R, are able to induce PI3K/Akt/mTOR signaling pathway via downregulating Beclin1. In parallel, they showed, by in situ analysis of human NSCLC, that overexpression of IL-7/IL-7R and mTOR plays an important role in decreasing lung cancer cell autophagy and increases tumor development [ 134 ].…”
Section: Myokines and Autophagymentioning
confidence: 99%
“…IL-7 and its receptor IL-7R, are able to induce PI3K/Akt/mTOR signaling pathway via downregulating Beclin1. In parallel, they showed, by in situ analysis of human NSCLC, that overexpression of IL-7/IL-7R and mTOR plays an important role in decreasing lung cancer cell autophagy and increases tumor development [ 134 ].…”
Section: Myokines and Autophagymentioning
confidence: 99%
“…Recent studies indicated that the expression of Beclin1 and mTOR were well correlated with survival and clinical stages of human non-small cell lung cancer (NSCLC) patients. Indeed, IL-7 activates PI3 K/Akt/mTOR signaling pathway via Beclin1 to regulate autophagy in lung cancer cells (Jian et al, 2019). What is more, it has been reported that Beclin1 was up-regulated in 67.7% of NSCLC patients, and was suggested that high Beclin-1 expression predicts longer survival in locally advanced NSCLC (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-7 (IL-7) has been detailed to the required for both B-cell and T-cell proliferation and its lack would result in immature immune cell arrest. IL-7 can modulate cell growth, as well as apoptosis and modulate cancer lymphangiogenesis [41][42]. Apoptosis is a form of programmed cell death.…”
Section: Discussionmentioning
confidence: 99%